Public Policy Innovation in The Digital Era: A Systematic Literature Review Study - Dede Hermansah; Hendri Arditya; Alfarul Dwi Gagas P; Ilyasa Diswara Firdaus; Devy Siti Khofifah (Siber Nusantara Research, 2026)
Digital transformation is driving significant changes in governance and public services. This study aims to analyze the development of research on public policy innovation in the digital era using the Systematic Literature Review (SLR) method with the PRISMA approach. Data was obtained from the Scopus, ScienceDirect, Emerald Insight, Google Scholar, and Garuda databases using keywords related to public policy innovation and digital transformation. Based on the PRISMA selection process, 35 articles were obtained that met the inclusion criteria for analysis. The results of the study show that the main themes of the research include digital transformation of government, digital-based public service innovation, e-government implementation, and smart governance. Digitalization of government has been proven to improve bureaucratic effectiveness, quality of public services, transparency, and data-driven decision-making. However, its implementation still faces challenges such as limited technological infrastructure, low digital literacy, bureaucratic resistance, and data security. This study also found a research gap related to digital collaboration and evaluation of the effectiveness of government digital policies.